Gas exchanges of tomato hybrids cultivated in protected environments and open field - Rocha, Ruy de Carvalho; Oliveira, Gertrudes Macario de; Rodrigues, João Domingos; Leitão, Mário de Miranda Vilas Boas Ramos; Carvalho, Adheilton Rogers Pilé de (Agrometeoros, 2018)
The effects of adverse climate constrain vegetable production, and protected cultivation has shown to be a promising technique in maximizing yield. However, protected environments might change with meteorological elements, particularly solar radiation, consequently affecting gas exchanges. The aim of this study was to assess gas exchanges of tomato hybrids cultivated in different environments in the Sub-medium region of the São Francisco River Valley. The experiment was conducted from August to December 2006, in the experimental area of DTCS/ UNEB, Juazeiro, BA, in a 5 x 2 (environments x tomato hybrids) factorial experiment design with randomized blocks with ten treatments and four replicates. The factor environment was subdivided in open field and four covered environments with shading screens, and tomato hybrids were C-5240 e D-4768. Gas exchanges were evaluated in the period ranging from October 24 to 10, 2006 (flowering/ fruiting stage). Variables analyzed were: PAR radiation, net CO2 assimilation rate, leaf transpiration rate, stomatal conductance, and leaf temperature. There was significant difference between tomatoes cultivated in open field and in protected environments for all variables, except for leaf temperature. Regardless of type of cover, there was a positive effect of shading on decreased PAR radiation compared to open field, in favor of gas exchanges, under the climatic conditions of the Sub-medium region of the São Francisco River Valley.